Hotels, prices and risk premium in exceptional times: The case of Milan hotels during the first COVID-19 outbreak - Anastasia Arabadzhyan; Paolo Figini; Lorenzo Zirulia (Annals of Tourism Research Empirical Insights, 2021)
The COVID-19 outbreak affects hotels by changing demand and supply. We investigate the case of Milan, the outbreak epicentre in Europe, by studying the hotels' reaction before, during, and after the lockdown. We monitor room offers and prices posted on Booking.com in January–September 2020. Findings suggest that: i) the reaction at the beginning of the pandemic was a fall in prices; ii) the number of active hotels dropped with the lockdown, while prices stabilised, a fact that we attribute to fairness considerations; iii) hotels managed uncertainty by increasing the free cancellation options and the risk premium, especially for short-term leads; iv) news and expectations on the pandemic, and the introduction of travel limitations, were essential drivers of managerial decisions.